Association of ApoVLDLII Gene Polymorphism with Body Composition Traits in Kampung Chicken - Furqon, A.; Gunawan, A.; Ulupi, N.; Suryati, T.; Sumantri , C. (International Journal of Poultry Science, 2017)
Background and Objective: Very low density lipoproteins (VLDLs) is a major class of lipoprotein particles that is synthesized and secreted by the liver. Selection for economic traits based on molecular marker assisted selection are required to increase production performance. The present study was designed to analyze associations of very low density Apo lipoprotein II (ApoVLDLII) gene polymorphisms with body composition traits. Kampung chicken, a native chicken in Indonesia, is slow-growing chicken. Materials and Methods: A total of 76 male Kampung chickens were used in the current study. Body compositions were measured in 12 and 26 weeks of age. Primers for intron 1 region were designed from genomic chicken sequence. A G634A SNP of the ApoVLDLII gene intron 1 region was detected and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was then used for genotyping of Kampung chicken population. Results: The ApoVLDLII polymorphism was significantly associated with body, carcass, breast, thigh, back and thigh muscle weight in 26 weeks old Kampung chicken population (p